A Reliable and Efficient Highway Multihop Vehicular Broadcast Model. (8th February 2012) - Chuan, Deng; Jian, Wang
Abstract : A reliable and efficient highway broadcast model based on gain prediction is proposed to solve excessive information retransmission and channel conflict that often happen to flooding broadcast in vehicular ad hoc network. We take accountofthe relative speeds, the intervehicle distance, and the coverage difference of the neighboring vehicles into predicting the gain of every neighbor, and further select the neighbor with the maximum gain as the next hop on the every direction of road. Simulations show that the proposed model is clearly superior to the original flooding model and a recent variant based on mobility prediction in packet arrival rate, average delay, forwarding count, and throughput.